STATUS, DISTRIBUTION AND HABITAT SPECIFICITY OF BENTHIC MACRO-INVERTEBRATES: A CASE STUDY IN FIVE TRIBUTARIES OF BUDDHIGANGA RIVER IN WESTERN NEPAL - Bhandari, Bipul; Shah, Ram Devi Tachamo; Sharma, Subodh (Journal of Institute of Science and Technology, 2019)
Benthic macro-invertebrates are organisms that inhabit the bottom of substrates such as sediments, debris, logs, macrophytes and filamentous algae of streams, rivers and lakes for some span of their lifecycle. They are important part of food chain since they are source of food for different species of fishes and process organic matters. These organisms are considered vital tools to assess any environmental change caused by anthropogenic interference in the river ecosystems. In this study, we sampled macro-invertebrates from 5 different rivers across altitudinal ranges of 600- 800 m and 1500-1700 m above sea level. We observed that the macro-invertebrate diversity varied substantially across altitudinal ranges. The diversity of macro-invertebrates was higher in lower altitudinal range, where 11 families were found, more than the higher altitudinal range. Some rare and dominant families were also identified in our study. We also examined the substrate specificity of macro-invertebrates. Results revealed that Ephemeroptera,Tricoptera, Coleoptera, Diptera and Odonata were found in all seven substrates namely bedrock, boulder, cobble, stone, pebble, gravel and sand. The richness and abundance of macro-invertebrates were documented in cobble, stone and pebble substrates. Similarly we also investigated the ecological river quality class of rivers using Ganga River System Biotic Score-Average Score per Taxon (GRS-BioS/ASPT) system which indicated good status. The outcomes of this study serve as a baseline data since no prior research has been done in these rivers.